Palaeokarst characteristics and effects on reservoirs in the fourth member of Leikoupo Formation, Longmen Mountain front, western Sichuan Basin - Yong LI; Meizhou DENG; Guorong LI; Hengyi GAO; Qiongxian WANG; Sai HE (Shiyou shiyan dizhi, 2021)
Dolostones of tidal flat facies are the major reservoir rock type of the fourth member of Leikoupo Formation, Longmen Mountain front, western Sichuan Basin. The reservoir controls are dominated by phase belt, dolomitization and denudation. Core observation, cast thin section identification, laser carbon and oxygen isotopes, cathode luminescence, electron probe and inclusion thermometry were used to study the denudation effect. This reservoir went through three periods of denudation, including penecontemporaneous period, epidiagenetic period and buried period, which separately formed intragranular and moldic pores, gypsum caves, and fault-line cavities. The studies of karstification and gypsum dissolution in the paleo-epigenetic period showed that, the distinguishing signs of meteoric water impacts in episode I of the Indosinian Movement include the irregular network of weathering cracks, karst and gypsum breccia, de-anointed calcite maintaining gypsum board shape or right-angle edge shape, widely developed paste mold holes and paste-dissolved holes. These products are featured by low carbon and oxygen stable isotope values, a wide range of strontium isotope values, low content of Sr-Mn-Fe-K-Na trace elements, low-temperature single-phase water-soluble inclusions. The dissolution of gypsum in episode I of the Indosinian Movement is the key for reservoir generation.